Effects of chitin and chitosan extracted from house cricket (Brachytrupes portentosus Lichtenstein) on performance and immune response of broiler chickens - Busayo, Ibitoye E. (2018)
By 2022, the worth of feed additive in the global market would be over US$11 billion. Chitin (CT) and chitosan (CS) are potential feed additives and are biologically beneficial. However, studies have concentrated mainly on crustacean CT and CS; data on their effects on growth performance and immune response in poultry are inconsistent, while information on the use of CT and CS from other sources in poultry production is unavailable. The present study therefore aims at evaluating the effects of dietary cricket and shrimp CT and CS on growth performance and immune response in broiler chickens. Chitin and chitosan were extracted from about 8-week old house cricket (Brachytrupes portentosus), using a chemical method, whereas shrimp CT and CS were commercially obtained. Then, both the cricket chitin (CCT) and chitosan (CCS) and shrimp chitin (SCT) and chitosan (SCS) were physicochemically analyzed for comparison. To study the effect of dietary CCT, CCS, SCT and SCS on the growth performance and immune response of broiler chickens, a total of 150 day-old male Cobb500 broiler chicks were randomly allotted into one of the five dietary treatments with three replicates. Birds in various treatments were fed as follow: treatments 1 (T1) basal diet alone; treatment 2 (T2) 0.5 g/kg diet CCT with basal diet; treatment 3 (T3) 0.5 g/kg diet CCS with basal diet; treatment 4 (T4) 0.5 g/kg diet SCT with basal diet; while treatment 5 (T5) were fed 0.5 g/kg diet SCS with basal diet. To evaluate the effect of the treatments on the gut health, the structural morphology of the villus height (VH) and crypt depth (CD) of the jejunum and duodenum were evaluated. In addition, relative mRNA expression of oligopeptide transporter (PepT1), excitatory amino acid transporters 3 (EAAT3), Na+-dependent glucose and galactose transporter (SGLT1) and Na+-independent fructose transporter (SGLT5) were determined from the jejunum by real-time PCR. Furthermore, in order to evaluate the immune response of the experimental birds to dietary CT and CS, weights of Bursa of Fabricius (BF) and spleen were evaluated and the relative expression of Toll-like receptor-4 (TLR-4), Toll-like receptor-15 (TLR-15), interleukin 1-β (IL-1β) and inducible nitric oxide synthase (iNOS) from the spleen of chickens were studied using real-time PCR. This study revealed that house cricket is a potential source of good quality CT and CS and that CCT and CCS are similar to SCT and SCS respectively. However, CCT is of purer and of better quality than the SCT. The feeding trials showed that dietary CT and CS at 0.5 g/kg have a significant (p<0.05) effect on body weight (BW), body weight gain (BWG) and body weight adjusted for gizzard and abdominal fat. The BW and BWG of experimental birds in T2 (CCT) differ non-significantly (p>0.05) from the control, while the BW and BWG of the broilers in T3 (CCS) and T5 (SCS) decreased significantly (p<0.05). Also, abdominal fat accumulation in the chickens under T2 (CCT) and T5 (SCS) reduced significantly (p<0.05). Study of the haematobiochemistry of broiler chickens showed that broilers under T5 (SCS) were markedly stressed, while those in T4 (SCT) in addition to being stressed were also anaemic with marked thrombocytopenia. More so, eosinophilia was observed in birds under T3 (CCS) and T5 (SCS). However, T2 (CCT) had no statistical adverse effect on haemopoiesis, while it also lower serum cholesterol and triglycerides of experimental broiler chickens. At day 21, dietary CT and CS had no statistical (p>0.05) effect on the index immune organs, while T4 (SCT) significantly reduced the weights of BF and spleen of broiler chickens at day 42. Nevertheless, broiler of T2 (CCT) and T5 (SCS) had improved BF and spleen similar to the control. The mRNA expressions of TLR- 4, TLR-15, IL-1β and iNOS were significantly (p<0.05) impacted in this study. At day 21 and relative to the control (T1), T5 (SCS) significantly up-regulated the gene expression of TLR-4 and IL-1β, while other treatments (T2, T3 and T4) nonsignificantly (p>0.05) down-regulated them. In addition, T2 (CCT), T4 (SCT) and T5 (SCS) numerically increased the expression of TLR-15, whereas, T3 (CCS) decreased it. More so, these treatments (T2, T3, T4 and T5) significantly decreased the gene expression of TLR-4, TLR-15 and iNOS at day 42. Treatments 3 (CCS), T4 (SCT) and T5 (SCS) significantly (p<0.05) improved the jejunal CD and VH:CD at day 21, while they were significantly improved by T4 (SCT) at day 42. The gut morphology of broiler chickens under T4 (SCT) was significantly (p<0.05) better than those of T2 (CCT). Moreover, at day 21 and relative to the control, dietary CT and CS significantly (p<0.05) down-regulated the relative gene expression of PepT1, EAAT3, SGLT1 and SGLT5, while only dietary CS (T3 and T5) at day 42 significantly (p<0.05) decreased the gene expression of PepT1, EAAT3, SGLT1 and SGLT5. Therefore, chickens in T2 (CCT) had a similar growth performance and immune response with the control, but better than those of T3 (CCS), T4 (SCT) and T5 (SCS). In addition, birds of T2 had the lowest abdominal fat accumulation in the chickens.